2020
DOI: 10.1007/s12070-020-01883-0
|View full text |Cite
|
Sign up to set email alerts
|

Modified Bhramari Pranayama in Covid 19 Infection

Abstract: The Coronavirus (2019-Cov-2) infection Covid-19 is highly contagious caused by single stranded RNA virus (?ssRNA) with nucleocapsid and spreading widely all across the world and responsible for more than 3.6 million morbidity and 0.25 million mortality No specific treatment is available till date. The clinical symptoms are mainly upper respiratory leading to diffuse viral pneumonia and multiple organ failure involving. Kidney, Liver and Heart along with coagulopathies. During 2004 (SARS-CoV) pandemic role of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…Also, practice of yoga has been reported to decrease inflammatory biomarkers including IL-6 21 . There is a recent report of practice of bhramari pranayama enhancing the release of nitric oxide that prevents coagulopathies and morbidity in Coronavirus Disease (COVID-19) 34 . Thus, increased plasma NO level by deep and slow breathing pranayamas in the present study could have prevented the development of hypertension and cardiometabolic risks and decreased the inflammatory milieu in pregnant women having risk of GH.…”
Section: Discussionmentioning
confidence: 99%
“…Also, practice of yoga has been reported to decrease inflammatory biomarkers including IL-6 21 . There is a recent report of practice of bhramari pranayama enhancing the release of nitric oxide that prevents coagulopathies and morbidity in Coronavirus Disease (COVID-19) 34 . Thus, increased plasma NO level by deep and slow breathing pranayamas in the present study could have prevented the development of hypertension and cardiometabolic risks and decreased the inflammatory milieu in pregnant women having risk of GH.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric Oxide (NO) inhibits viral protein and RNA, as well as NO synthase reduces progeny virus output by 82%, reducing corona virus replication by virtue of its antiviral impact. It is hypothesized that, in addition to humming, eating alkaline meals high in dietary nitrates, which the body can convert to NO, boosts NO expression and carbon dioxide through longer expiration, preventing coagulopathies and morbidity caused by COVID-19 ( 230 ). Fresh juice free of preservatives from the aforementioned vegetables, or antioxidants derived from purple carrot and cabbage, in combination with appropriate anti-coagulants, may help prevent or mitigate the negative effects of COVID-19 pathological outcomes, as well as mitigate multi-organ damage caused by COVID-19 during the ongoing pandemic ( 231 ).…”
Section: Personal Habits As a Key Tool To Rejuvenate The Immune Systemmentioning
confidence: 99%
“…Even in 12-week yoga-based program, a significant increase in eNOS and total nitric oxide concentrations were noticed (p<0.05) [17]. Regarding nitric oxide syntheses enhancement, Taneja MK has proposed modified Bhramari Pranayama use along with other modes in the treatment of COVID-19 as it is suggested that humming promotes nitric oxide production [18]. [19].…”
Section: Main Partmentioning
confidence: 99%